Analysis of Multi-Year Expenditure Budgets of Metropolitan Municipalities with Grey Prediction Model: An Application on Istanbul Metropolitan Municipality - Akçakaya, Onur (Fırat University, 2021)
The fact that the revenues and expenditures of local governments are not predictable interrupts the strategic planning process and affects financial autonomy negatively. In this context, how to make the expense budget predictable in local governments is an important problematic. The purpose of the study is to examine how convenient the Grey Prediction Method can be used in estimating the expense budgets of metropolitan municipalities. In this framework, the expenditure budget of the Istanbul Metropolitan Municipality (IMM) is analyzed for the 2021-2024 period. A two-stage pathway was followed in the study. First of all, it has been tested whether the results are consistent or not by applying the Grey Prediction Method to IMM's data between 2018-2020. At this stage, the deviation rate was determined as 1.88%, indicating that the method is valid and reliable. As a matter of fact, considering that the deviation rate between the current estimates made by IMM and the actual figures is at a high level of 12%, the deviation rate of the study is at a reasonable level. Considering this determination, the second stage was passed and the method was applied again for expenditure-budget estimation for the period between 2021-2024. According to the findings obtained, the total expenditure budget of IMM is estimated as 29.492.566.776 TL for 2021, 33.321.097.278 TL for 2022, 37.646.622.359 TL for 2023 and 42.533.658.577 TL for 2024.

Yerel yönetimlerin gelir ve giderlerinin öngörülebilir olmaması, stratejik planlama sürecini sekteye uğrattığı gibi mali özerkliği de olumsuz etkilemektedir. Bu bağlamda, yerel yönetimlerde gider bütçesinin nasıl öngörülebilir kılınabileceği önemli bir sorunsaldır. Bu çalışmanın amacı, Gri Tahmin Yöntemi’nin büyükşehir belediyelerinin gider bütçelerinin tahmininde kullanılmaya ne denli elverişli olabileceğinin incelenmesidir. Bu çerçevede, İstanbul Büyükşehir Belediyesi’nin (İBB) gider bütçesi, 2021-2024 dönemi için analiz edilmektedir. Çalışmada iki aşamalı bir yol izlenmiştir. Öncelikle İBB’nin 2018-2020 yılları arasındaki verilerine Gri Tahmin Yöntemi’nin uygulanmasıyla sonuçların tutarlı olup olmadığı test edilmiştir. Bu aşamada sapma oranı, yöntemin geçerli ve güvenilir olduğunu gösterecek şekilde %1.88 olarak tespit edilmiştir. Nitekim İBB’nin hali hazırda yaptığı tahminler ile gerçekleşen rakamlar arasındaki sapma oranının %12 gibi nispeten yüksek bir seviyede olduğu göz önünde bulundurulduğunda, çalışmanın sapma oranı makul seviyededir. Bu tespit, göz önünde bulundurularak ikinci aşamaya geçilmiş ve yöntem tekrar uygulanarak kuruluşun 2021-2024 yılları arasındaki döneme ilişkin gider-bütçesi tahminlemesi yapılmıştır. Elde edilen bulgulara göre, İBB gider bütçesi toplamı, 2021 yılı için 29.492.566.776 TL, 2022 yılı için 33.321.097.278 TL, 2023 yılı için 37.646.622.359 TL ve 2024 için 42.533.658.577 TL olarak tahmin edilmiştir.
BÜYÜKŞEHİRLERİN ÇOK YILLI GİDER BÜTÇELERİNİN GRİ TAHMİN MODELİ İLE ANALİZİ: İSTANBUL BÜYÜKŞEHİR BELEDİYESİ ÖRNEĞİNDE BİR UYGULAMA